157k views
0 votes
6. Use the remainder theorem to find P(-3) for P(x) = x³+4x²+4

6. Use the remainder theorem to find P(-3) for P(x) = x³+4x²+4-example-1

1 Answer

4 votes

STEP - BY - STEP EXPLANATION

Given:


P(x)=x^3+4x^2+4

Step 1

Suppose x= -3, then

x+ 3

Step 2

Divide the polynomial by (x+ 3)

Step 3

Determine the remainder and quotient from the above.

Quotient = x²+ x - 3

Remainder = 13

ANSWER

Quotient = x²+ x - 3

Remainder = 13

6. Use the remainder theorem to find P(-3) for P(x) = x³+4x²+4-example-1
User Tborenst
by
5.0k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.